Regulating Emotional Responses to Climate Change – A Construal Level Perspective - Ejelöv, Emma; Hansla, André; Bergquist, Magnus; Nilsson, Andreas (Frontiers in Psychology, 2018)
This experimental study (N = 139) examines the role of emotions in climate change risk communication. Drawing on Construal Level Theory, we tested how abstract vs concrete descriptions of climate threat affect basic and self-conscious emotions and three emotion regulation strategies: changing oneself, repairing the situation and distancing oneself. In a 2 × 2 between subjects factorial design, climate change consequences were described as concrete/abstract and depicted as spatially proximate/distant. Results showed that, as hypothesized, increased self-conscious emotions mediate overall positive effects of abstract description on self-change and repair attempts. Unexpectedly and independent of any emotional process, a concrete description of a spatially distant consequence is shown to directly increase self-change and repair attempts, while is has no such effects when the consequence is spatially proximate. “Concretizing the remote” might refer to a potentially effective strategy for overcoming spatial distance barriers and motivating mitigating behavior.